Regional markets of medical services: specifics of formation and provision in the conditions of medical reform (Regional aspects of productive forces development of Ukraine, 2020)
Introduction. The article substantiates the scientific principles of forming the market of medical services, which would meet the global challenges and needs of reforming the domestic medical industry, would take into account the trends of decentralization. The structural blocks of the market of medical services are identified and the specifics of administration of their provision in modern conditions with the use of contractual and contractual forms are analyzed.Goal. The goal is to substantiate the essential determinants and applied aspects of the formation of the medical services market, taking into account the needs of decentralization and improving the administration of their provision through a system of agreements and contracts.Methods. Methods of system, structural-logical, comparative analysis and generalization are used in the scientific publication.Results. The scientific approaches to the formation of the market of medical services at the regional level are substantiated, the peculiarities of the organization of their provision through the prism of concluding agreements and contracting are verified. Emphasis is placed on the fact that regional health care markets will be the best way to improve the provision of resources for the provision of medical services, their innovation, thus improving the quality, reducing the financial risks of providing and receiving medical services, increasing the responsible attitude of the population to their health.Conclusions. The main provisions of the scientific article will contribute to the formation of a competitive market for medical services, improve the quality of their provision and strengthen public health.